Targeting nonsense-mediated RNA decay does not increase progranulin levels in the GrnR493X mouse model of frontotemporal dementia - Denise M. Smith; Michael L. Niehoff; Karen Ling; Paymaan Jafar-Nejad; Frank Rigo; Susan A. Farr; Miles F. Wilkinson; Andrew D. Nguyen (PLoS ONE, 2023)
A common cause of frontotemporal dementia (FTD) are nonsense mutations in the progranulin (GRN) gene. Because nonsense mutations activate the nonsense-mediated RNA decay (NMD) pathway, we sought to inhibit this RNA turnover pathway as a means to increase progranulin levels. Using a knock-in mouse model harboring a common patient mutation, we tested whether either pharmacological or genetic inhibition of NMD upregulates progranulin in these GrnR493X mice. We first examined antisense oligonucleotides (ASOs) targeting an exonic region in GrnR493X mRNA predicted to block its degradation by NMD. As we previously reported, these ASOs effectively increased GrnR493X mRNA levels in fibroblasts in vitro. However, following CNS delivery, we found that none of the 8 ASOs we tested increased Grn mRNA levels in the brains of GrnR493X mice. This result was obtained despite broad ASO distribution in the brain. An ASO targeting a different mRNA was effective when administered in parallel to wild-type mice. As an independent approach to inhibit NMD, we examined the effect of loss of an NMD factor not required for embryonic viability: UPF3b. We found that while Upf3b deletion effectively perturbed NMD, it did not increase Grn mRNA levels in Grn+/R493X mouse brains. Together, our results suggest that the NMD-inhibition approaches that we used are likely not viable for increasing progranulin levels in individuals with FTD caused by nonsense GRN mutations. Thus, alternative approaches should be pursued.